Are women and providers satisfied with antenatal care? Views on a standard and a simplified, evidence-based model of care in four developing countries - Ba'aqeel Hassan; Carroli Guillermo; Al-Mazrou Yagob; Farnot Ubaldo; Miguel Belizán José; Al-Osimi Muneera; Rojas Georgina; Kuchaisit Chusri; Piaggio Gilda; Nigenda Gustavo; Romero Mariana; Villar José; et al. (BMC, 2002)
Abstract Background This study assessed women and providers' satisfaction with a new evidence-based antenatal care (ANC) model within the WHO randomized trial conducted in four developing countries. The WHO study was a randomized controlled trial that compared a new ANC model with the standard type offered in each country. The new model of ANC emphasized actions known to be effective in improving maternal or neonatal health, excluded other interventions that have not proved to be beneficial, and improved the information component, especially alerting pregnant women to potential health problems and instructing them on appropriate responses. These activities were distributed within four antenatal care visits for women that did not need any further assessment. Methods Satisfaction was measured through a standardized questionnaire administered to a random sample of 1,600 pregnant women and another to all antenatal care providers. Results Most women in both arms expressed satisfaction with ANC. More women in the intervention arm were satisfied with information on labor, delivery, family planning, pregnancy complications and emergency procedures. More providers in the experimental clinics were worried about visit spacing, but more satisfied with the time spent and information provided. Conclusions Women and providers accepted the new ANC model generally. The safety of fewer visits for women without complications with longer spacing would have to be reinforced, if such a model is to be introduced into routine practice.